Mengajarkan Ekoprint yang Kreatif dan Ramah Lingkungan Kepada Peserta Didik PAUD di Kecamatan Katingan Kuala Kabupaten Katingan - Sumiati, Sumiati (FKIP Universitas Palangka Raya, 2024)
This research aims to teach ecoprinting techniques to Early Childhood Education (PAUD) children in Katingan Kuala District, Katingan Regency, and assess the impact of this activity on their creativity, environmental awareness and fine motor skills. Ecoprint is a fabric dyeing technique using natural materials such as leaves, flowers, stems and plant roots, which offers an environmentally friendly and educational approach to learning. This activity involved 20 children from five different PAUDs aged between 4 and 6 years. Research methods include preparing fabric with mordant, selecting and arranging natural materials by children, wrapping and steaming the fabric, as well as drying and opening the ecoprint results. The research results show that ecoprint activities have succeeded in increasing children's enthusiasm for learning, with each stage of the activity showing active participation and high focus. The research results showed a significant increase in creativity, environmental awareness, and fine motor skills in PAUD students. Educators also report that these activities help children develop critical thinking and collaboration skills. Apart from that, ecoprints also provide a deeper understanding of nature and natural processes, and instill important values ​​such as patience and perseverance.